A Methodology for Identifying Critical Success Factors and Performance Measurement for Sustainable Schools - Hekimoglu, Ihsan; Ozgen, Dogan; Sen, Ceyda (MDPI, 2025)
There are conflicting findings in the literature regarding the factors that influence school success. This uncertainty complicates the effective allocation of resources. The present study aims to identify critical success factors (CSFs) for schools by incorporating the perspectives of various stakeholders and addressing this gap in the literature. Additionally, a comprehensive performance measurement model is developed to ensure the sustainability of success. A three-phase complementary methodology was employed with 330 participants, including school administrators, students, and parents, from 23 high schools in Istanbul. Fuzzy cognitive mapping (FCM) was utilized to identify critical success factors (CSFs) by calculating centrality index values. Additionally, a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis was conducted to assess the institutional context, and a balanced scorecard (BSC) was developed for performance measurement. According to the results from FCM and SWOT analysis, the factors related to teachers, students, and school physical conditions were identified as the most critical success factors. The BSC model was employed in four high schools, yielding performance scores of 81.12 and 92.52, 67.89, 77.58, respectively. With its unique methodological approach integrating three analytical techniques, this study highlights the critical role of teacher experience, student quality, and appealing physical conditions in school success. It offers school administrators a scientifically grounded, practical performance evaluation tool. This study is significant as it establishes a foundation for monitoring large-scale investment performance in schools, encompassing Environmental, Social, and Governance (ESG) dimensions, and providing a basis for sustainability initiatives within educational institutions.
Keywords: measuring sustainability; critical success factors; sustainable schools; ESG; performance measurement; FUZZY COGNITIVE MAPS; BALANCED SCORECARD; SWOT ANALYSIS; STRATEGY; Science & Technology - Other Topics; Environmental Sciences & Ecology